Implementation of Local Economic Management to Improve the Welfare of the People of Sibolga City - Kaharuddin Kaharuddin; Fauziah Nur Simamora (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the implementation of local economic management in improving the welfare of the people of Sibolga City. The method used is qualitative with a case study approach through in-depth interviews, observations, and FGD on fishermen, market traders, MSME actors, and policy makers. The results of the study show that the implementation of local economic management is still sectoral and has not been integrated. The level of fishermen's welfare is relatively low with an average income of IDR 1,850,000 per month, while fostered MSME actors experience a 15-20% increase in income. The main inhibiting factors include weak coordination across agencies and lack of infrastructure. In conclusion, it is necessary to establish a local economic forum and prepare a regional regulation on people's economic empowerment to realize sustainable community welfare.